2018
DOI: 10.1002/fld.4515
|View full text |Cite
|
Sign up to set email alerts
|

Development of temporal and spatial high‐order schemes for two‐fluid seven‐equation two‐pressure model and its applications in two‐phase flow benchmark problems

Abstract: Summary Current existing main nuclear thermal‐hydraulics (T‐H) system analysis codes, such as RALAP5, TRACE, and CATHARE, play a crucial role in the nuclear engineering field for the design and safety analysis of nuclear reactor systems. However, two‐fluid model used in these T‐H system analysis codes is ill posed, easily leading to numerical oscillations, and the classical first‐order methods for temporal and special discretization are widely employed for numerical simulations, yielding excessive numerical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The V-shaped linear advection test is a benchmark problem that has been widely used to verify the accuracy of numerical algorithms. 27 The main parameters of the test section and test conditions are shown in Table 1. The test section is a horizontal pipe.…”
Section: V-shaped Linear Advection Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The V-shaped linear advection test is a benchmark problem that has been widely used to verify the accuracy of numerical algorithms. 27 The main parameters of the test section and test conditions are shown in Table 1. The test section is a horizontal pipe.…”
Section: V-shaped Linear Advection Testmentioning
confidence: 99%
“…A stable and monotone high‐order discretization scheme can be obtained by using a bounded nonlinear slope limiter which makes the total variation diminish (TVD). Our previous study 27 showed that the Van Albada 28 high‐order spatial scheme, which satisfies the TVD condition, is the most accurate discretization scheme. Thus, it is used in this research and the slope limiter is ψ(r)goodbreak=r(rgoodbreak+1)r2+1.$$ \psi (r)=\frac{r\left(r+1\right)}{r^2+1}.…”
Section: Numerical Algorithmmentioning
confidence: 99%
“…Many applications of the fluids in sciences or engineering are made such as: the developments of the fluid models where the robustness and accuracy have been checked and evaluated with six major two-phase flow benchmark problems [16]. These problems involve two linear advection problems, the problem of oscillation for the liquid column, the problem of a ransom water faucet, the reversed water faucet problem, and the problem of the two-phase shock tube where all of them are fundamental in the nuclear engineering T-H field.…”
Section: Introductionmentioning
confidence: 99%